Biodiversity integrity indicator and threshold of minimum 10–20% of land for conservation in agricultural landscapes - CGIAR Research Program on Water, Land and Ecosystems (2020)
Uptake by Earth Commission and EU Green Deal policies of recommendations on planetary boundary conditions for sustainable biodiverse agriculture.